Addition of Liposome Bupivacaine to Bupivacaine HCl Versus Bupivacaine HCl Alone for Interscalene Brachial Plexus Block in Patients Having Major Shoulder Surgery. Issue 3 (May 2017) - Vandepitte, Catherine; Kuroda, Max; Witvrouw, Richard; Anne, Ludwig; Bellemans, Johan; Corten, Kristoff; Vanelderen, Pascal; Mesotten, Dieter; Leunen, Ine; Heylen, Micheline; Van Boxstael, Sam; Golebiewski, Monika; et al.
Abstract : Background and Objectives: We examined whether liposome bupivacaine (Exparel) given in the interscalene brachial plexus block lowers pain in the setting of multimodal postoperative pain management for major shoulder surgery. Methods: Fifty-two adult patients were randomized to receive either 5 mL of 0.25% bupivacaine HCl immediately followed by 10 mL of liposome bupivacaine 133 mg (n = 26) or 15 mL of 0.25% standard bupivacaine alone (n = 26) in interscalene brachial plexus block. The primary outcome (worst pain in the first postoperative week) was assessed by the Modified Brief Pain Inventory short form. Secondary outcomes were overall satisfaction with analgesia (OBAS), functionality of the surgical arm, sleep duration, time to first opioid (tramadol) request and opioid consumption (mEq), sensory-motor block characteristics, and the occurrence of adverse effects. Results: Worst pain was lower in patients given liposome bupivacaine added to standard bupivacaine than in patients given standard bupivacaine alone (generalized estimating equation [GEE] estimated marginal mean values, 3.6 ± 0.3 vs 5.3 ± 0.4 points on the Numeric Rating Scale, respectively, although the effect was modest, 1.6 ± 0.5; 95% confidence interval, 0.8–2.5). Total OBAS scores indicated greater satisfaction (GEE estimated marginal mean values, 1.8 ± 0.3 vs 3.3 ± 0.4 on total OBAS, respectively, with modest effect, difference, 1.4 ± 0.5; 95% confidence interval, 0.5–2.4). There were no differences in any of the other secondary outcomes. Conclusions: Liposome bupivacaine added to standard bupivacaine may lower pain and enhance patient's satisfaction in the first postoperative week even in the setting of multimodal analgesia for major shoulder surgery. This study was registered with clinicaltrials.gov (NCT02554357) on July 11, 2015, by Principal Investigator Catherine Vandepitte, MD. Abstract : Supplemental digital content is available in the text.